European strategies for early intervention in stroke: (part 2 of 2); a report of an Ad Hoc Consensus Group Meeting - Hacke, Werner (Cerebrovascular diseases, 1996)
Stroke is a major cause of death and disability in industrialized countries, but stroke awareness is still generally poor and treatment often ill-defined. At a meeting of a European Ad Hoc Consensus Group, the following recommendations for acute stroke management were made. Need for education: There is a clear need for stroke awareness to be increased. Use of the terms 'brain attack' and 'brain infarction', appropriately translated into the major European languages, can aid this process. The major target groups for educational programmes should be the public, particularly those at risk and their spouses and relatives, and paramedical staff. Media campaigns that inform the public what to do and where to go/contact if a stroke occurs could significantly reduce the time to presentation. Acute stroke care should not be promoted too aggressively or prematurely before an adequate infrastructure is in place to successfully administer modern evidence-based therapies. Organization of acute stroke care: Stroke is a medical emergency. A stroke unit offers the most effective acute stroke care in terms of both mortality and short- and long-term morbidity, and may thereby both improve outcome and lower costs. A stroke team is an acceptable alternative in areas where a dedicated stroke unit is not available. Optimal acute stroke care: General guidelines should be provided on the flow of decision-making and urgent care, with specific instructions for each stage and event in acute stroke. It is essential that all stroke patients are admitted to hospital quickly, ideally within the first 1-2 h. Ways must be established to reduce transition times within the local setting when patients and/or emergency services contact a variety of different physicians and hospitals. The minimum emergency investigations necessary for differential diagnosis of stroke are computed tomography (CT), Doppler ultrasonography, electrocardiography (ECG) and blood tests. These must be available 24 h/day and be performed without delay. General medical measures should be instituted as necessary, even before CT scanning, with reference to the potential particular complications of acute stroke. Acute stroke patients should be monitored continuously or at frequent intermittent intervals throughout the first 24 h with respect to blood pressure, ECG, respiration, temperature and oxygen saturation. In carefully selected patients, thrombolysis with recombinant tissue plasminogen activator (rt-PA) may be indicated (if approved by regional registration agencies). This must be administered under specialist supervision, and on a dedicated intensive care or intensive stroke care unit. Careful selection of eligible patients is paramount. Thrombolysis with streptokinase is not recommended, due to the excessive risk of haemorrhage. If these measures and early secondary prevention are implemented, it will be possible to improve stroke outcome and reduce the cost of acute and chronic stroke care. New agents for acute stroke treatment, e.g. the neuroprotectants currently being evaluated in phase III trials, should also contribute to improved outcomes.
Elektronische Reproduktion der Druck-Ausgabe 26. Mai 2010
Gesehen am 03.06.2025